Environmental and individual correlates of leisure-time physical activity in Ghana: a cross-sectional study - Akwaboah, Patrick Kwame (International Journal Of Community Medicine And Public Health, 2025)
Background: Leisure-time physical activity (LTPA) offers significant health benefits yet remains the least engaged domain of overall physical activity in sub-Saharan Africa. Limited evidence exists regarding how environmental and individual factors impact LTPA, particularly among healthcare professionals. This study explored the correlates of LTPA among Physician Assistants in Ghana, with a major focus on natural environmental conditions. Methods: Data from a cross-sectional survey conducted among 439 Physician Assistants in Ghana between October and December 2024 was used. Participants reported their levels of LTPA using a revised Global Physical Activity Questionnaire. Climate data, including temperature, wind direction, rainfall, and humidity, from the Ghana Meteorological Agency were matched to participants’ practice regions. An adjusted linear regression was used to examine the relationship between LTPA and individual/environmental correlates. Results: The mean weekly moderate-to-vigorous-intensity physical activity was 179.3±18.3 minutes. Overall, 69% of respondents did not meet the recommended 150 minutes per week of activity levels by the World Health Organization. In adjusted models, each one-percentage-point increase in relative humidity was associated with an additional 10 minutes of LTPA per week (β =10.4, 95% CI: 1.9 to 18.9). Conversely, wind direction (β =-35.4, 95% CI: -57.3 to -13.5) and male gender (β =-112.9, 95% CI: -190.8 to -35.0) were associated with lower LTPA. Conclusions: Climatic factors significantly influence LTPA in the Ghanaian setting. The findings underscore the need for context-specific interventions that consider climate variability and gender disparities in promoting active lifestyles.